A single locus with a large effect on virulence in Nectria haematococca MPI - B. T. Hawthorne; J. Rees-George; J. Bowen; R. D. Ball (Fungal Genetics Reports, 1997)
Analysis of the pathogenicity of 800 progeny from a HI-path (Blue) x LO-path (Cream) cross showed that the quantitative genetic control of pathogenicity in Nectria haematococca MPI on hypocotyls of Cucurbita maxima was determined by 6-12 ‘effective factor’ or quantitative trait loci (QTL). In addition there was evidence for a virulence/colony colour gene(s) with an effect that was superimposed on the pathogenicity phenotype.